Hydrodeoxygenation and pyrolysis of free fatty acids obtained from waste rendering fat - Martyna Murat; Jaromír Lederer; Alena Rodová; José Miguel Hidalgo Herrador (Eclética Química, 2020)
Non-edible fats are a common renewable feedstock for the biofuels production to avoid partially the use of edible feeds and fossil fuels. The aim of this work was the use of waste rendering fat to produce pyrolyzed and hydrogenated oils. The feedstock was hydrolyzed producing free fatty acids and glycerol + residues. The free fatty acids were pyrolyzed (with and without metal sulfides metal supported catalyst) or hydrotreated separately. An autoclave closed hermetically in nitrogen (pyrolysis) or hydrogen (hydrotreatment) atmosphere was used. Gaseous products were analyzed by GC‑FID/TCD. Liquid products were analyzed by Simulated Distillation (ASTM D2887) and FT-IR (attenuated total reflectance technique). For the pyrolysis, the main gaseous products were carbon dioxide, methane, ethane, and propane. For the hydrotreatment, the total amount of gases produced was much lower being the main product the carbon dioxide. For liquids, the hydrotreatment of the free fatty acids produced the respective hydrocarbons by decarboxylation reaction and the pyrolysis produced a mixture of compounds with lighter boiling ranges compared to the original free fatty acids. The use of a metal sulfide metal supported catalyst in the pyrolysis led to a higher amount of hydrogen production. but similar boiling range liquid products compared to the non-catalytic test.